Sto lat polskiego handlu zagranicznego – uwarunkowania, najważniejsze trendy, partnerzy i produkty - Wąsiński, Marek (Sprawy Międzynarodowe, 2018)
This paper gives a short overview of one hundred years of Polish history in the area of trade on the occasion of the centenary of Poland regaining its independence. Four periods – the interwar period, decades of the Polish People’s Republic, the transition period from 1989 to 2004 and Polish membership in the European Union – are analysed to show that during these one hundred years, Poland had to build its trade and economy from scratch thrice. The paper focuses on the most important trends and looks into the geographic and product structures of trade. Unsurprisingly, the results show that the most dynamic growth and the most positive changes are observed in Polish trade during its membership in the European Union.